Diet quality of adolescents in rural Sri Lanka based on the Diet Quality Index–International: findings from the 'Integrating Nutrition Promotion and Rural Development' project. Issue 10 (1st April 2019) - Williams, Julianne; Townsend, Nick; Rayner, Mike; Jayawardena, Ranil; Katulanda, Prasad; Manoharan, Seenithamby; Wickramasinghe, Kremlin
Abstract: Objective: The current paper describes methods of evaluating dietary habits of Sri Lankan adolescents based on the Diet Quality Index–International (DQI-I), which has been used in multiple international studies to describe dietary variety, moderation, adequacy and balance. The paper describes the method for calculating DQI-I scores and examines associations between DQI-I scores and dietary intake, and between DQI-I scores and sociodemographic factors. Design: The study followed a three-stage cluster randomised sampling method. Dietary intake was collected using a validated FFQ. Estimated micronutrient intakes and number of servings consumed were described according to DQI-I quartiles. DQI-I scores were tabulated according to sociodemographic characteristics. Multilevel modelling was used to examine associations between sociodemographic characteristics and DQI-I scores. Setting: Secondary schools in rural Sri Lanka. Participants: Adolescents ( n 1300) aged 12–18 years attending secondary school in rural Sri Lanka. Results: DQI-I scores increased with consumption of fat (% energy), cholesterol (mg/d), energy (kJ/d), protein (% energy), Na (mg), dietary fibre (g), Fe (mg) and Ca (mg), but decreased according to percentage of energy coming from carbohydrates. DQI-I scores were significantly lower among females and students with lower levels of maternal education. Conclusions: Policies are needed to increase the availability and affordability of nutrient-rich foods such as fruits, vegetables and high-protein foods, particularly to students from lower socio-economic backgrounds. Significant differences in diet quality according to sex, socio-economic status and district suggest there is potential for targeted interventions that aim to increase access to affordable, nutrient-rich foods among these groups.